Accessing DNA Damage in Chromatin: Preparing the Chromatin Landscape for Base Excision Repair - Rodriguez, Yesenia (DNA Repair (Amst), 2015)
DNA damage in chromatin comes in many forms, including single base lesions that induce base excision repair (BER). We (and others) have shown that the structural location of DNA lesions within nucleosomes greatly influences their accessibility to repair enzymes. Indeed, a difference in the location of uracil as small as one-half turn of the DNA backbone on the histone surface can result in a 10-fold difference in the time course of its removal in vitro. In addition, the cell has evolved several interdependent processes capable of enhancing the accessibility of excision repair enzymes to DNA lesions in nucleosomes, including post-translational modification of histones, ATP-dependent chromatin remodeling and interchange of histone variants in nucleosomes. In this review, we focus on different factors that affect accessibility of BER enzymes to nucleosomal DNA.